Determinants of Firm Value: The Role of Capital Structure, Leverage, Growth, Dividend Policy, and Profitability in Property Companies Listed on the IDX - Sartika, Sartika; Perdana, Aditya; Saputri, Eka Julianti Efris; Efrina, Liona (Jurnal Akuntansi & Keuangan Unja, 2026)
This research aims to analyze the influence of capital structure, leverageleverage, company growth, dividend policies, and profitability on the value of companies in the property and real estate sectors listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. This sector was chosen because of its strategic role in the national economy and its positive growth amid global pressure. The value of the company, as an indicator of the performance and attractiveness of investors, is influenced by the internal financial conditions that reflect the sustainability of the business. Using a quantitative approach and data from 23 property and real estate companies that meet the sample criteria of the total population of 92 companies, analyzed using multiple linear regression with softwareIBM SPSS software. The results showed that the structure of capital, leverage, dividend policy, and profitability had a significant effect on the value of the company, supporting signal theory. However, the growth of the company has no significant influence, in contrast to some previous studies. This research provides empirical evidence of the factors that determine the value of the company in the property and real estate sectors in Indonesia, which can be a consideration for management, investors, and subsequent researchers.